(untitled) (The Journal of Forensic Accounting Profession, 2021)
Groups of companies have existed ever since the early 20th century in the legal and economic terms. Over time, their concept was complemented, both in legislation and in the corporate practice. The issue of establishing and managing groups of companies is regulated by the corporate legislation. It particularly regulates the concept of the controlling and subsidiary company, company with mutual shares, holding, concern, association of companies and other forms of company associations. In terms of the legal definition, these are associated companies composed of two or more companies that are affiliated to each other as follows: by share in equity or membership interests (equity-related companies), by contract (contract-related companies); by equity and contract (mixed-related companies). These associated companies include a parent company and one or more subsidiary companies, which may be related by equity, contract or both. Besides the general concept of the associated companies, the author aims to point to the liability in a common activity as a group of companies. A particular attention is drawn to the legal treatment and obligations resulting from the International Accounting Standards and binding financial statements related to them. (Previously published on Sciendo: https://sciendo.com/article/10.2478/jfap-2021-0005, pod licencom CC BY-NC-ND 4.0)